Manajemen Aliran Kas Dan Dampaknya Terhadap Nilai Perusahaan - Dwi Widya Pratiwi; Nurzi Sebrina; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to determine the effect of cash flow management on firm Value. Researchers tested manufacturing companies listed on the Indonesia Stock Exchange in 2017-2018 with a total sample of 101 samples using a purposive sampling method. In this study, the firm’s value is measured using Tobin's Q ratio. Analysis technique used Panel EGLS (Cross-section random effects) analysis. The first model investigates of the three component cash flow measures (days of sales outstanding, days of inventory outstanding and days of payable outstanding), and the last two models investigate the cash conversion cycle and operating cash cycle metrics, respectively. Thechange (Δ) in one variable for period t is that measured by the differences between at the end of the quarter and at the end of the previous quarter’s value. The results showed that days of sales outstanding, days of inventory outstanding, cash conversion cycle and operating cash cycle have a significant effect on firm value.